The Dynamic Landscape of Interfaith Marriage in Indonesia: Navigating The Supreme Court Circular Letter (SEMA) No. 02 of 2023 and Population Administration Law - Sri Maryati; Achmad, Hudzaifah; Adang Darmawan Achmad; Mohd Anuar Ramli (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The issue of interfaith marriage in Indonesia is rooted in the legal conflict between Article 2, paragraph (1) of Law No. 1/1974 on Marriage, which regulates the legality of marriage based on religious law, and Articles 34 and 35 of Law No. 23/2006 on Citizenship Administration. Articles 34 and 35 of Law No. 23/2006 state that a valid marriage is one that is reported and registered, with Article 35(a) stipulating that the court determines the validity of a marriage. The incompatibility of these regulations regarding interfaith marriages has affected legal interpretation, resulting in discrepancies in judicial decisions. In response, the Supreme Court issued Circular Letter No. 2 of 2023, providing guidance for judges in adjudicating cases involving the registration of marriages between individuals of different religions and beliefs. This circular aims to ensure certainty and consistency in the application of the law in such cases. However, this regulation has sparked debate among legal experts. This research adopts a qualitative approach and is analyzed descriptively. The findings indicate that conflicting legal interpretations regarding interfaith marriages lead to differences of opinion among judges on the validity of such marriages. Moreover, inconsistencies in the legal framework governing interfaith marriage in Indonesia result in conflicts of legal interpretation. The primary cause of the ineffectiveness of Indonesia's interfaith marriage law is due to substantive legal considerations. Disagreements between legal systems lead to disputes among legal entities and impact interfaith marriages within society.